What Barriers? What Bridges? - and Holling, C.S. (Barriers and Bridges to the Renewal of Ecosystems and Institutions, 1995)
This volume uses a series of case studies to test an emerging theory of complex adaptive systems that forms the basis for explaining the interrelated dynamics of ecosystems, institutions and society. It deals equally with institutional organization and ecosystem structure.